2012
DOI: 10.4236/ajac.2012.312106
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of 1-Palmitoyl-2-oleoyl-<i>sn</i>-glycero-3-phosphoethanol and Ethyl Glucuronide in Human Umbilical Cord

Abstract: In utero exposure to ethanol continues to be a significant public health issue and neonatal healthcare professionals are in need of objective means to identify exposed newborns. The aim of this study was to fully validate two methods for the detection of two direct alcohol biomarkers, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanol (POPE) and ethyl glucuronide (EtG), in umbilical cord and apply the assays to a group of authentic specimens. The limits of detections were 2 and 1 ng/g for POPE and ETG and the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Clean Screen EtG columns (United Chemical Technologies, Bristol, PA) [34, 35] failed to retain EtS under all tested acidic loading conditions (10 % hydrochloric acid, trifluroacetic acid, acetic acid, and formic acid). An anion exchange approach [25, 37, 38], offered efficient sample clean-up and sufficient EtS extraction efficiency (Table 4), obtaining a low 2.5 ng/g LOQ. Lower EtS extraction efficiency compared to EtG was most likely due to strong sulfate group retention on the quaternary amine SPE phase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Clean Screen EtG columns (United Chemical Technologies, Bristol, PA) [34, 35] failed to retain EtS under all tested acidic loading conditions (10 % hydrochloric acid, trifluroacetic acid, acetic acid, and formic acid). An anion exchange approach [25, 37, 38], offered efficient sample clean-up and sufficient EtS extraction efficiency (Table 4), obtaining a low 2.5 ng/g LOQ. Lower EtS extraction efficiency compared to EtG was most likely due to strong sulfate group retention on the quaternary amine SPE phase [25].…”
Section: Discussionmentioning
confidence: 99%
“…DBS was stored at room temperature in a bloodspot drying box prior to shipment. Specimens were analyzed at United States Drug Testing Laboratories using a previously published method (Jones et al, 2012). The method monitored a single isomer of PEth (palmitoyl/oleoyl), which is a phospholipid containing 16:0 and 18:1 fatty acids and is the most prevalent PEth homologue in human blood (Faller et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The DBS papers were shipped to the U.S. for PEth testing. PEth detection on the DBS samples was conducted by United States Drug Testing Laboratories (USDTL; Des Plaines, IL, US) using a previously published method (Jones et al, 2011), using LC-MS/MS. The most prevalent PEth homolog (16:0/18:1) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…A handful of studies have compared PEth results to self-reported alcohol use in diverse populations with varying results (Stewart et al, 2010; Bajunirwe et al, 2014; Jain et al, 2014; Francis et al, 2015). PEth can conveniently be tested from dried blood spots (DBS; Jones et al, 2011) and may be useful to corroborate or supplement results on unhealthy alcohol consumption obtained by self-report from FSW and their male clients.…”
Section: Introductionmentioning
confidence: 99%